Managing amidst rapid change : management approaches for dynamic environments - Collyer, Simon (Project Management Institute, 2015)
The ability to deliver value in dynamic environments has become an essential skill for today's project managers given the ever increasing rates of change driven by deregulation, the information age, and globalization. Managing Amidst Rapid Change responds to this new reality with specific management techniques that refine the theory of how best to handle projects significantly challenged by dynamism. Combining management research with advice from experienced practitioners across 10 industries, and interspersed with analyses of case studies from Google, NASA, and IBM, to name just a few, this practitioner-focused book proposes a new theoretical model for managing rapid change in projects.